Analisis VECM Implementasi Zakat, Infaq dan Shodaqoh pada Hasil Pertanian Padi di Desa Tanggul Wetan - Maghfiro, Nur Faizah; Lutfi’ah, Hikmatul (KUBIS, 2024)
Tanggul District is one of the Districts in Jember Regency, the majority of the people in this District work as rice farmers, but the low understanding of the farming community in Tanggul Wetan Village causes the payment of zakat to be adjusted to existing beliefs regardless of who is obliged to receive zakat. Besides that, ZIS payments are also determined by several factors. The purpose of this study was to find out The relationship between factors that influence farmers in carrying out ZIS obligations from rice agricultural products in Tanggul Wetan Village.The sampling method used in this research is purposive sampling method. The results of this study indicate that 1) The factors that can affect the implementation of ZIS in Tanggul Wetan Village, Tanggul District from the results of the VECM test are as follows: a) Short term: the factor that can affect the implementation of ZIS is the Income factor (Y), because the value t statistic > t critical, with the t statistic equation |-2.34404| > t critical |2.0301|. b) Long term: a factor that can influence the implementation of ZIS is the Education factor (X2), because the t statistic > t critical, with the equation t statistic |-11.5565| > critical t value |2.0301|. c) The religiosity factor and farmer group activity factor are not significant in influencing the implementation of ZIS in Tanggul Wetan Village